Evaluating Computer Service Store Governance and Service with COBIT 5: EDM01 and APO09 - Sabrila, Trifebi Shina; Ilmiyanor, Akhmad Hafi; Yanti, Hardi; Maretmy, Angella; Latif, Abdul; Lindawati, Ratna (LPPM Universitas Sari Mulia, 2024)
This study aims to analyze the application of the EDM01 (Ensuring the Setup and Maintenance of the IT Governance Framework) and APO09 (Managing Service Agreements) domains of the COBIT 5 framework in the context of computer service stores. Through survey methods and direct interviews, data is collected to evaluate the maturity level of the governance process and IT services in the store. The results of the analysis show that both process domains are at maturity level 2 (Managed), indicating that the process is well managed but still has potential for improvement. An evaluation of the gap between current and expected conditions reveals potential improvements in process consistency and effectiveness. These findings provide insights into how to improve service quality and operational efficiency in computer service shops, as well as ensure better customer satisfaction through the implementation of COBIT 5 best practices. This research provides a solid foundation for computer service shops to improve their IT governance in accordance with industry standards and meet business needs more effectively and efficiently.